ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF D2-40 MARKER IN HIGH-GRADE DYSPLASIA, MICROINVASIVE AND FRANKLY INVASIVE ORAL SQUAMOUS CELL CARCINOMA - Rehan, Syeda Areeba; Rashid, Wajeeha; Rahat, Manahil (Journal of Ayub Medical College Abbottabad, 2024)
Background: Oral squamous cell carcinoma (OSCC) is a prevalent malignancy that develops through a series of stages, ranging from high-grade dysplasia (HGD), microinvasive OSCC (MiOSCC) to frankly invasive OSCC. However, sometimes it is difficult to differentiate HGD from MiOSCC and invasive OSCC in histopathological morphology on routine staining. The aim of the study was to assess the expression patterns of D2-40 in these distinct stages of oral carcinogenesis, providing insights into its potential role as a biomarker for disease progression. Methods: This cross-sectional study was carried out in the Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi, Pakistan, from 1st Dec 2023 to 5th Feb 2024. It involved the application of a D2-40 immunohistochemical marker on a total of thirty tissue samples, ten patients diagnosed with High-grade dysplasia (HGD), ten with Microinvasive Oral squamous cell carcinoma (OSCC), and ten invasive OSCC cases. SPSS was used for data analysis and a p-value < 0.05 was considered significant. Results: The mean age of patients was 60.47±11.78 years, males were affected more (70%). D2-40 was expressed in different stages of oral carcinogenesis in increasing order as in 40% in HGD (4/10), and 90% in both microinvasive (9/10) and invasive OSCC (9/10) lesions. D2-40 IHC expression was associated with the patient’s age and disease. Conclusion: Podoplanin (D2-40) has the potential to be a novel biomarker for the timely identification of microinvasion in early oral epithelial pathologies with diagnostic dilemmas.